2007
DOI: 10.1111/j.1365-2672.2007.03393.x
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of Staphylococcus aureus following treatment with the antibacterial flavonol galangin

Abstract: Aim:  The flavonol galangin, an antimicrobial constituent of the traditional medicines propolis and Helichrysum aureonitens, is being assessed as part of an ongoing investigation into the antibacterial activity of flavonoids. The present study sought to establish whether galangin has any aggregatory effect on bacterial cells. Methods and Results:  In preparatory time‐kill assays, 50 μg ml−1 of galangin was found to reduce colony counts of c. 5 × 107 CFU ml−1Staphylococcus aureus NCTC 6571 by approximately 15 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(94 citation statements)
references
References 28 publications
2
91
0
1
Order By: Relevance
“…Such methods have frequently been used to test flavonoids and on many occasions bactericidal activity was reportedly detected [30,32,59]. Studies with model membranes indicate that flavonoids cause aggregation though [60,61], and in 2007 it was confirmed that the flavonol galangin has this effect on bacterial cells [62]. The flavan-3-ol epicatechin gallate has also been reported to cause bacterial aggregation [19], although it is not yet clear whether this observation was due to genuine aggregation (cells clumping together) or pseudomulticellular bacteria (cells failing to separate following binary fission [54]).…”
Section: Identification Of Flavonoid Activity As Bacteriostatic or Bamentioning
confidence: 98%
“…Such methods have frequently been used to test flavonoids and on many occasions bactericidal activity was reportedly detected [30,32,59]. Studies with model membranes indicate that flavonoids cause aggregation though [60,61], and in 2007 it was confirmed that the flavonol galangin has this effect on bacterial cells [62]. The flavan-3-ol epicatechin gallate has also been reported to cause bacterial aggregation [19], although it is not yet clear whether this observation was due to genuine aggregation (cells clumping together) or pseudomulticellular bacteria (cells failing to separate following binary fission [54]).…”
Section: Identification Of Flavonoid Activity As Bacteriostatic or Bamentioning
confidence: 98%
“…C'est la galangine qui semble donner l'effet antistaphylococcique. Elle agirait en empêchant l'adhésion de ce germe [13]. La propolis brésilienne (ou propolis rouge) est antimicrobienne, en particulier sur S. aureus ATCC 25923 et S. mutans [2].…”
Section: Activité Antibactérienneunclassified
“…An aggregation of bacterial cells was previously shown with other compounds that originated from plants, such as the flavonoids galangin and catechin (60). An aggregation of Salmonella on leaves contributes not only to the persistence of the pathogen on the plant but also to its resistance to disinfection approaches (61).…”
Section: Figmentioning
confidence: 99%